Safety and Predictive Factors of Short-Term Efficacy of a Single Injection of Mannitol-Modified Cross-Linked Hyaluronic Acid in Patients with Trapeziometacarpal Osteoarthritis. Results of a Multicentre Prospective Open-Label Pilot Study (INSTINCT Trial). Issue 11 (15th June 2018) - Dauvissat, Jérémy; Rizzo, Christophe; Lellouche, Henri; Porterie, Jérôme; Melac-Ducamp, Sylvie; Locquet, Vincent; Travers, Vincent; Maillet, Bernard; Conrozier, Thierry
Purpose: To assess safety and search predictive factors of efficacy of a single intra-articular injection of a mannitol-modified hyaluronic acid (HA) viscosupplement, in patients having trapeziometacarpal (TMC) osteoarthritis (OA). Methods: Patients with symptomatic TMC OA, not adequately relieved by analgesic therapy and/or by the use of a thumb splint, were included in a 3-month prospective multicentre open-label trial. All underwent plain radiographs with the Kapandji incidences allowing the Dell radiological grade assessment (1-4). Primary end point was the variation between injection (D0) and day 90 (D90) of the thumb pain (11-point Likert scale). Treatment consisted in a single injection of 0.6 to 1 mL of a viscosupplement made of a cross-linked HA combined with mannitol. All injections were performed under imaging guidance. Predictive factors of pain decrease were studied in univariate and multivariate analysis. Results: A total of 122 patients (76% women, mean age 60, mean disease duration 36 months) were included and 120 (98%) were assessed at 3 months. The TMC OA was of Dell's grade 1, 2, 3, and 4 in 23%, 36.8%, 36.8%, and 3.5% of cases, respectively. At D0, the average (SD) pain level was 6.5 ± 1.6 without significant difference between Dell groups ( P  = .21). At day 90, pain decreased from 6.5 ± 1.6 to 3.9 ± 2.5 (difference −2.7 ± 2.5; −42%; P  < .0001) without significant difference between Dell grade ( P  = .055), despite a seemingly smaller number of responders in stage 2 patients. The average analgesic consumption decreased in more than 1 out of 2 patients. In multivariate analysis, no predictor of response was identified. There was no safety issue. All adverse events (11%) were transient increase in pain during or following HA administration and resolved without sequel within 1 to 7 days. Conclusions: This study suggests that a single course of HANOX-M-XL injection is effective in relieving pain in patients with TMC OA, without safety concern. Patients with advanced stage of OA benefit the treatment as much as those with mild or moderate OA.